Desain Kaos Geometri sebagai Media Pemahaman Konsep Bentuk pada Segiempat untuk Siswa Sd Kelas III: Geometry T-Shirt Design as a Media for Understanding the Concept of Forms Quadrangle for Elementary School Students Grade III - Frida Murtinasari; Dwi Noviani Sulisawati; Lut fiyah (Emasains : Jurnal Edukasi Matematika dan Sains, 2019)
The problem of misconceptions about flat building in geometry, especially quadrilateral, has been very frequently reviewed by practitioners and educational researchers. However, this remains an inherent problem to date and results in confusion of the basic concept of quadrilaterals. Therefore in this study a geometry-themed learning media was created, especially quadrilateral in the form of geometric t-shirt design to make it easier for students to understand the definitions and differences between the quadrilateral itself. Based on the results of the study, it was found that geometric T-shirt learning media was declared valid with a score above 3 or in the good category. Whereas for the fulfillment of practical criteria, a value of 3.5 is obtained, which means that the shirt of geometry does not require revision and is practical. The value of effectiveness is effective, where the results obtained that the geometry shirt provides learning outcomes that have a significant effect on the achievement of the defined KKM and the achievement of a positive response of 97.12% by students. So that the geometry T-shirt learning media is declared valid, practical and effective in accordance with the criteria for developing instructional media.